Findings from a three-round Delphi study: essential topics for interprofessional training on complementary and integrative medicine - Angelika Homberg; Nadja Klafke; Svetla Loukanova; Katharina Glassen (BMC, 2020)
Abstract Background Integrating complementary medicine into medical care promotes patient-oriented care. A well-informed and collaborative professional healthcare team is essential for effective and patient-safe implementation of these methods. At present, the skills for patient counseling, therapy and care regarding complementary medicine vary among the professional groups involved. Professionals generally feel that they are not sufficiently qualified in this area. Curricular concepts for Complementary and Integrative Medicine (CIM) are virtually non-existent in undergraduate interprofessional training. The aim of this study is to initiate a consensus-building process between various experts (professionals, students, patient and faculty representatives) in order to identify which topics should be the focus of such a curriculum. Methods A three-round Delphi study was carried out from March 2018 to March 2019 to compile the experience and knowledge of experts in the field of integrative patient care and interprofessional education. Sixty-five experts from Germany and German-speaking Switzerland with various professional backgrounds and experiences were asked to name general content, therapy methods and treatment reasons which should be addressed in interprofessional seminars. In the subsequent rounds these were rated on a seven-point Likert scale. The ratings were assigned to relevance groups and discussed in a final workshop in July 2019. Results The response rates for the three rounds were 76% (n = 50), 80% (n = 40) 90% (n = 36); and 21% (n = 11) for the final workshop. The experts suggested that topics could be aligned along the most common treatment reasons such as insomnia, generalized pain, fatigue and back pain. However, it is important that students also receive an overview of the evidence base for different therapeutic concepts, especially in the field of classical natural medicine, acupuncture and mind-body medicine, and that they get an overview of the effects and interactions of frequently used procedures. Conclusion Consensus was reached among the various experts on the most important topics for an interprofessional CIM curriculum. The systematic evaluation of the topics in this study can help to create a curriculum that achieves a high level of acceptance among teachers, lecturers and students, and thus facilitates implementation at universities and medical faculties.